Initial Experience with the Gore® Acuseal Graft for Prosthetic Vascular Access. Issue 5 (September 2014) - Tozzi, Matteo; Franchin, Marco; Ietto, Giuseppe; Soldini, Gabriele; Carcano, Giulio; Castelli, Patrizio; Piffaretti, Gabriele
Purpose: The purpose of this study is to report the short-term results of the Gore ® Acuseal graft for prosthetic vascular access (pVA) in patients with end-stage renal disease on hemodialysis. Methods: Between October 2011 and October 2013, all the consecutive patients who underwent implantation of a new expanded Polytetrafluoroethylene (ePTFE) tri-layer graft were included in the study. Primary and secondary patency rate, time to first cannulation, and complications were recorded. Follow-up was performed at 1, 3, 6, and 12 months after the intervention. Results: Thirty ePTFE tri-layer heparin bonded grafts were implanted in 18 males and 12 females. The graft configuration was radial-basilic (n=12, 40%), brachial-basilic (n=10, 33.3%), femoro-femoral (n=3, 10.0%), radial-cephalic (n=2, 6.7%), radial-antecubital forearm (n=2, 6.7%), and brachial-axillary (n=1, 3.3%). No patient was lost during a mean follow-up time of 6.3±5.9 months (range, 1-24; median, 5). Mean time to first cannulation was 2.4±1.2 days (range, 1-15). Primary functional patency rate was 68.0% ± 10 at 6 and 12 months. Secondary patency rate was 93.3% ± 6 at 6 and 12 months. Pseudoaneurysm, bleeding, seroma, or graft infection was never observed. Conclusions: In our experience, the Gore ® Acuseal graft was useful and safe. Early cannulation was always performed, and structural complications did not occur. Primary functional and secondary patency rate are satisfactory in the short term.